DEVELOPING COMPETENT APPROACH OF STUDENTS BY IMPROVING TEST ASSIGNMENTS. - Uchqurova Zarina Shavkatovna; Mamatqulov Doniyor Anvarovich (Scholar Express Journal, 2021)
The article gives insights about developing a competent approach by students by improving test assignments. And also, it indicates ongoing research with respect to assessing the quality of biology teacher education. Thus, tests in the teaching of natural sciences and assessing students’ knowledge have been learnt.
Keywords: Natural sciences; test; assignment; assessment